Quality assurance implementation and challenges in selected Malaysian public universities - Njie, Baboucarr (2014)
The quest to improve, propelled by governments, institutions and concerned stakeholders has become the lifeline in higher education prompting many universities to wake up to this reality. Malaysia, no exception to this premise, has correspondingly responded with the dramatic upsurge of its universities in particular and tertiary education in general by expending huge resources and effort towards quality improvement and monitoring. This study was conducted with the aim of exploring the void between quality assurance policies and all those requirements and results it is expected to achieve on one hand and how superficially they view and agree or otherwise with the quality management practices and what they would have done different if they had the chance of taking charge of quality from design to implementation. The objective of the study was to examine quality assurance implementation in two selected Malaysian public universities, explore how quality assurance practices are understood by stakeholders as well as the extent of their involvement and to explore the challenges of implementation of quality assurance processes and the purposes viewed as essential for the enhancement of current quality assurance practices in public universities in Malaysia. For the purposes of achieving an in depth understanding of the nature of quality assurance practices, application and challenges, the qualitative approach which is characteristic for prying deep into a phenomenon was the chosen research methodology. With a view to understand the meaning of quality assurance practices, a complex phenomenon with its multifaceted challenges, the case study approach with its three pronged approach was chosen for a more comprehensive and holistic inquiry.A total of fourteen respondents comprising six Quality assurance officials and eight academic staff of two public universities were interviewed. Four dominant themes emerged: commitment to address quality for actualization of educational goals; differences in scope of understanding quality assurance; application of quality system as a means to an end; and challenges and nurturing quality culture. The results reveal an existence of strong policies by the government and the Universities under review, backed by material support and units specifically tasked with quality management and improvement with strict evidence of adherence to a generic quality management system called the ISO among other professional quality frameworks. The findings also reveal differences in understanding levels of quality between the two categories of staff studied which largely impacts on the views held by the two and culminate to the application of quality assurance as a means to an end by academic staff. The findings further reveal a cause and effect rationalization of challenges of quality assurance as well as a general concordance among the two categories of the challenges of nurturing quality culture. The study concludes on a recommendation that the whole philosophy of quality assurance needs to be realigned with some local and ownership flair added in order for the stakeholders to embrace it as theirs and give it the necessary attention it deserves to serve its intended purpose. In addition, vital processes of the quality management cycle especially the planning phase need to involve key stakeholders like academic staff whose experience and thoughts can build into the framework for ease of adherence and acceptance purposes.